tRNA selectivity during ribosome-associated quality control regulates the critical sterility-inducing temperature in two-line hybrid rice - Can Zhou; Chunyan Liu; Bin Yan; Jing Sun; Shengdong Li; Ji Li; Jia Wang; Xiahe Huang; Wei Yan; Shuying Yang; Chenjian Fu; Peng Qin; et al. (Proceedings of the National Academy of Sciences, 2025)
The two-line hybrid rice system, a cutting-edge hybrid rice breeding technology, has greatly boosted global food security. In thermo-sensitive genic male sterile (TGMS) lines, the critical sterility-inducing temperature (CSIT; the temperature at which TGMS lines change from male fertile to complete male sterile) acts as a key threshold. We recently uncovered that thermo-sensitive genic male sterility 5 ( tms5 ), a sterile locus presenting in over 95% of TGMS lines, leads to the overaccumulation of 2′,3′-cyclic phosphate (cP)-ΔCCA-tRNAs and a deficiency of mature tRNAs, which underlies the molecular mechanism of tms5 -mediated TGMS. However, there are a few reports on the regulatory mechanism controlling CSIT. Here, we identified a suppressor of tms5 , an amino acid substitution (T552I) in the rice Rqc2 (ribosome-associated quality control 2), increases the CSIT in tms5 lines through its C-terminal alanine and threonine modification (CATylation) activity. This substitution alters tRNA selectivity, leading to the recruitment of different tRNAs to the A-site of ribosome and CATylation rate by OsRqc2 during ribosome-associated quality control (RQC), a process that rescues stalled ribosomes and degrades abnormal nascent chains during translational elongation. Further, the mutation restores the levels of mature tRNA-Ser/Ile to increase the CSIT of tms5 lines. Our findings reveal the origin of overaccumulated cP-ΔCCA-tRNAs in tms5 lines, further deepening our understanding of the regulatory network in governing CSIT of TGMS lines containing tms5.